Profil Pasien dengan Gangguan Elektrolit yang Dirawat di Ruang Perawatan Intensif - Sumule, Vania S. P.; Laihad, Mordekhai L.; Kambey, Barry I. (Universitas Sam Ratulangi, 2025)
Abstract: Electrolyte disturbance is a common health problem in critical patients in the Intensive Care Unit (ICU). These disorders can cause serious complications and contribute to increased morbidity and mortality. This study aimed to determine the description of electrolyte disturbances experienced by patients in the ICU of Prof. Dr. R. D. Kandou Hospital. This was an observational study with a retrospective design involving 252 patients admitted to the ICU with electrolyte disturbances from January to June 2023. Data were obtained from medical records and analyzed descriptively. The results showed that hyponatremia was the most common electrolyte disorder (65.1%), followed by hypokalemia (48%), hypochloremia (53.6%), hypocalcemia (61.5%), and hyperphosphatemia (40.5%). The highest incidence was in the age group >65 years (18.7% for hyponatremia and hypocalcemia). The majority of patients were male. The most common disease diagnosis was sepsis. In conclusion, hyponatremia and hypocalcemia are the main electrolyte disorders in critical patients in the ICU of Prof. Dr. R. D. Kandou Hospital. The high-risk group is elderly men with sepsis. Close monitoring of electrolytes needs to be done especially in patients with these conditions to prevent fatal complications. Keywords: electrolyte disturbance; hyponatremia; hypocalcemia Abstrak: Gangguan elektrolit merupakan masalah yang sering terjadi pada pasien kritis di Intensive Care Unit (ICU). Penelitian ini bertujuan mengetahui profil pasien dengan gangguan elektrolit di ICU RSUP Prof. Dr. R. D. Kandou. Jenis penelitian ialah observasional retrospektif dan pendekatan kuantitatif. Sampel penelitian ialah 252 pasien dengan gangguan elektrolit yang dirawat di ICU RSUP Prof. Dr. R. D. Kandou periode Januari-Juni 2023. Pengambilan sampel dilakukan secara purposive sampling. Variabel yang diteliti meliputi jenis gangguan elektrolit, karakteristik pasien (usia, jenis kelamin), diagnosis penyakit, dan lama rawat inap. Data dikumpulkan dari rekam medis dan dianalisis secara deskriptif. Hasil penelitian mendapatkan gangguan elektrolit terbanyak ialah hiponatremia (65,1%) dan hipokalsemia (61,5%). Kelompok usia >65 tahun (18,7%) dan laki-laki lebih banyak mengalami gangguan elektrolit, dan diagnosis tersering ialah sepsis. Rerata lama rawat inap pasien 1-7 hari. Simpulan penelitian ini ialah hiponatremia dan hipokalsemia merupakan gangguan elektrolit yang paling umum terjadi pada pasien ICU RSUP Prof. Dr. R. D. Kandou. Pasien usia lanjut dan sepsis berisiko tinggi mengalami gangguan elektrolit. Kata kunci: gangguan elektrolit; hiponatremia; hipokalsemia